Extraction of third molars effects on bite and tooth alignment - Leung, Marilyn A.
It is not the objective of this paper to expound on Multiloop Edgewise Archwire Technique (MEAW) treatment modalities which are utilized to correct said malocclusions but only to show the effect of removal of third molars on the bite, with or without treatment. This paper presents two clinical cases: 1. A skeletal open bite case treated with just third molar extractions as well but in conjunction witht the MEAW technique.
Keywords: Multiloop Edgewise Archwire Technique; Skeletal open bite; Skeletal Class III